World Bank Group Engagement in Upper-Middle-Income Countries : Evidence from IEG Evaluations - Independent Evaluation Group (World Bank, Washington, DC, 2017)
Middle-income countries (MICs)—the largest group of World Bank Group clients—are critical drivers of the world economy, but they remain vulnerable to global shocks. Addressing the development challenges facing MICs can generate positive externalities and transferable knowledge to lower income countries. According to the 2017 World Bank Group document, “Forward Look: A Vision for the World Bank Group in 2030—Progress and Challenges,” to meet its twin goals of eradicating extreme poverty and ensuring shared prosperity in a sustainable manner, the World Bank Group must sustain and evolve its engagement with MICs. This synthesis review focuses on the World Bank Group’s engagement with upper-middle-income countries (UMICs) and concludes that the Bank Group’s support to them remains highly relevant from two perspectives: helping these countries address their specific developmental challenges, and potentially having a valuable demonstration effect for other lower-income groups of World Bank Group clients. The more successful programs the World Bank Group supported were generally long duration and went well beyond the scope of a single investment loan or development policy loan. The World Bank Group’s willingness to sustain its engagement and build close relationships at the technical level contributed to successful outcomes. Despite this high relevance, important challenges remain in fully addressing some of the structural issues that underlie UMIC’s vulnerability to various shocks and in making progress that is more significant and sustained in several important development areas. The general perception is that World Bank Group financing is diminishing in UMICs, but the World Bank continues its important dialogue and engagement with UMICs despite this perception, covering a wide range of issues from fostering countercyclical policies, to building resilience, to financing large infrastructure projects, to catalyzing private sector participation. IEG evaluations consistently emphasized the high relevance of the World Bank’s analytic work in supporting reforms in UMICs and the high value that country stakeholders in UMICs assigned to its analytical work and technical assistance. Going forward, there is scope for further work on analyzing World Bank Group performance across various groups and subgroups of clients, including within narrower technical areas.